Odpowiedzi

Najlepsza Odpowiedź!
2009-11-13T19:07:30+01:00
A.)47+(-36)=47-36=11
b.)-21-53=-74
c.)12+(-35)=12-35=-23
d.)-(-28)-120+14-30=28-120+14-30=-108
e.)-62-(-49)-38-16=-62+49-38-16=-67
f.)6-(-71)-39+11=6+71-39+11=49
2009-11-13T19:07:43+01:00
47+(-36)= 47-36= 11
-21-53=(-21) + (-53)= -74
12+(-35)= 12 - 35= -23
-(-28)-120+14-30= 28 -150 + 14= 42-150= -108
-62-(-49)-38-16= -62 + 49 -54=-116+49=-67
6-(-71)-39+11=6+71+11-39=88-39=49
2009-11-13T19:08:05+01:00
A.)47+(-36)=47-36=11
b.)-21-53=-74
c.)12+(-35)=12-35=-23
d.)-(-28)-120+14-30=28-120+14-30=42-150=-108
e.)-62-(-49)-38-16=-62+49-38-16=-116+49=-67
f.)6-(-71)-39+11=6+71-39+11=88-39=49